Desarrollo de la sensopercepción através de la implementación de una granja escolar para los alumnos de la escuela “Túpac Yupanqui “en la comunidad Llactahurco parroquia de Cusubamba perteneciente a la provincia de Cotopaxi durante el año 2013 - Pruna Herrera, Juan Gabriel (2014)
Today education requires educational training tools where the student can experiencing from the reality of their context interdisciplinary knowledge understanding of different areas of study to exercise greater commitment and responsability in their educational work. Thereby enabling coexistence and reciprocity of the educational process. Pedagogical models now assume more responsibility within the educational environment, because it is looking for a direct and active participation of students, teachers and the community in general, with the new implementation of productive projects pretending with this meaningful learning only must be achieved, with the practice itself or with the daily experiences of the students involved in this process.